2019
DOI: 10.26432/1809-3019.2019.64.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade de vida em pacientes oncológicos pós internação em UTI / Evaluation of quality of life in cancer patients after hospitalization in ICU

Abstract: Objetivo: Avaliar a qualidade de vida dos pacientes oncológicos pós-internação em Unidade de Terapia Intensiva Adulto. Metodologia: Trata-se de um estudo exploratório, descritivo, de corte transversal e com abordagem quantitativa. A amostra foi composta por 23 pacientes oncológicos que passaram por internação na UTI. A qualidade de vida foi avaliada através do instrumento genérico Medical Outcomes Study 36 – Item Short – Form Health Survey – SF 36. Resultados: A média dos escores nos domínios do SF 36 apresent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The WHO 2016 estimated that pain in almost 90% of cancer patients could be controlled with simple interventions [ 74 ]; however, many studies demonstrate that pain control in these cases is difficult. For example, in the study of 114 American oncology units with 810 individuals, 25% of the participants reported that most of the time, they lived with constant or intense pain that impacted their life and appeared to impair their quality of life [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO 2016 estimated that pain in almost 90% of cancer patients could be controlled with simple interventions [ 74 ]; however, many studies demonstrate that pain control in these cases is difficult. For example, in the study of 114 American oncology units with 810 individuals, 25% of the participants reported that most of the time, they lived with constant or intense pain that impacted their life and appeared to impair their quality of life [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expected result highlights these issues, considering the disease-caused limitations, the effects of treatments, the pain, and restrictions imposed by COVID-19 with social isolation. Physical limitations may include loss of function, muscle atrophy, and reduced range of motion; in addition, in chemotherapy or radiotherapy, fatigue can be one of the main consequences [ 47 , 74 ], which in clinical practice is undervalued, but negatively impacts the quality of life and survival of individuals [ 104 ].…”
Section: Discussionmentioning
confidence: 99%